Konformitas Teman Sebaya dan Price Discount: Membedah Pengaruhnya Terhadap Impulsif Buying Mahasiswa di Shopee - Anggi Nurnaimah; Yuyun Yunarti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In an era of increasingly growing consumption, students are one of the groups vulnerable to impulsive buying behavior, which is influenced by various factors, including peer conformity and Price discounts. Peer conformity encourages individuals to adjust their behavior to social groups in order to be accepted, while Price discounts are used as a marketing strategy to create urgency and increase product appeal, both of which can increase the likelihood of impulsive buying. This type of research uses a quantitative research method. The data in this study were collected by distributing questionnaires using a Likert scale to respondents. The sample in this study was determined using the Isaac and Michael formula. From a population of 767, a sample of 256 respondents was obtained. Data analysis was carried out using multiple linear regression through classical assumption tests, including validity, normality, heteroscedasticity, multicollinearity, and autocorrelation tests, before continuing with hypothesis testing using partial tests (t-test), simultaneous tests (F-test), and coefficient of determination tests. The results of the study indicate that the variables Peer Conformity (X1) and Price discount (X2) have a partial influence on impulsive buying (Y) and simultaneously show that the variables Peer Conformity (X1) and Price discount (X2) have a simultaneous influence on Impulsive Buying (Y).